Analysis of the Importance of Knowledge Management on Organizational Performance in the Digital Era - Indriyani Sinurat; Oslan Juliana Simbolon; Petra Aprianti Gultom; Miska Irani Tarigan (Global Economics: International Journal of Economic, Social and Development Sciences, 2025)
The digital era demands that organizations be fast-moving, adaptable, and innovative. With the advancement of information technology, changes in work methods, global competition, and stakeholder demands are becoming increasingly complex. Knowledge Management (KM) plays an important role as a strategic mechanism for identifying, acquiring, storing, sharing, and utilizing knowledge to improve organizational effectiveness and efficiency. In this context, knowledge management becomes one of the important elements for organizations to enhance performance. Knowledge management is not just about collecting data or information, but how organizations can store, share, create, and utilize knowledge to gain a competitive advantage. This article aims to analyze the importance of knowledge management for organizational performance in the digital age, including how the digital era changes the dimensions of knowledge management, how knowledge management contributes to organizational performance, the challenges faced, and their implications. The data obtained for this study were gathered from observations thru interviews with relevant parties and a literature review study by examining the results of empirical research from the past five years (2020–2025). The method used was descriptive literature analysis of 15 scientific articles from accredited national journals. The analysis focuses on the relationship between knowledge management dimensions (knowledge creation, storage, sharing, and application) and organizational performance indicators (financial performance, innovation, productivity, and customer satisfaction). The study results show that the implementation of knowledge management significantly contributes to improving organizational performance, both directly thru increased efficiency and effectiveness of work processes, and indirectly thru strengthening a culture of innovation and organizational learning. This article asserts that an organization's success in the digital age is not solely determined by its ability to adopt technology, but also by its ability to manage and leverage knowledge as a strategic resource. Therefore, knowledge management needs to be systematically integrated into the organization's digital strategy, accompanied by strengthening a learning culture, human resource training, and adaptive information technology systems.